Implicature in Emily in Paris Season 1 from the Perspective of Relevance Theory (LITPAM, 2025)
This study aims to analyze the utterances of the characters in the Emily In Paris season one series. Implicatures in the utterances are analyzed using the relevance approach as proposed by Sperber and Wilson. This study is a qualitative study. Data were collected using the observation and note-taking method. The data source used in this study was the dialogue from the Emily in Paris series. This study will use informal methods in presenting the results of data analysis. The results showed that in this series, the utterances of the characters in it contain various implicatures or implicit meanings, namely related to the differences in working hours culture between Emily and her co-workers, differences in clothing preferences between Emily and her boss, differences in perspectives on an advertisement between Emily and her co-workers, acceptance of a new culture between Emily and her co-workers, rejection of a new culture between Emily and her boss, Emily's comments on other people, namely Pierre Cadault, and Pierre Cadault's comments on himself. The implicatures of these utterances can be understood because of the relevance that connects the knowledge possessed by the speaker with the interlocutor about what is being said.